2015
DOI: 10.4067/s0718-58392015000500011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen and water deficit type on the yield gap between the potential and attainable wheat yield

Abstract: Water deficit and N fertilizer are the two primary limiting factors for wheat yield in the North China plain, the most important winter wheat (Triticum aestivum L.) production area in China. Analyzing the yield gap between the potential yield and the attainable yield can quantify the potential for increasing wheat production and exploring the limiting factors to yield gap in the high-yielding farming region of North China Plain. The Decision Support System for Agrotechnology Transfer (DSSAT) model was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Input factors are major driving forces of the spatial shift of grain production, as grain production is closely related to the input factors [36,41,42]. We analyzed statistical data of winter wheat input factors during 1998-2015 and found that there were significant differences in the changes of irrigation, chemical fertilizer application, and total mechanical power in different regions of the NCP.…”
Section: Input Factorsmentioning
confidence: 99%
“…Input factors are major driving forces of the spatial shift of grain production, as grain production is closely related to the input factors [36,41,42]. We analyzed statistical data of winter wheat input factors during 1998-2015 and found that there were significant differences in the changes of irrigation, chemical fertilizer application, and total mechanical power in different regions of the NCP.…”
Section: Input Factorsmentioning
confidence: 99%
“…The soil data for different sites were derived from the Resources and Environment Data Cloud Platform of the Chinese Academy of Sciences (http:// www.resdc.cn/), which included the mechanical composition of different soil layers, organic carbon content, pH, total nitrogen content, wilting coefficient, soil bulk density, saturated water content and other indicators. The relevant representative varieties, the crop yield data, crop management data, phenology and yields were collected from a 4-year experiment with five nitrogen (N) levels (0, 60, 120, 180 and 240 kg/ha) conducted during the 2008-2011 growing seasons in Wuqiao (Liu et al, 2015) and published journal articles (Hu et al, 2009;Jiang et al, 2009;Gong et al, 2013;Wang et al, 2013;Song, 2017;Zhang, 2018) for calibrating and evaluating the model in the seven sub-regions of the HFR. Of these data, 0.70 were used to calibrate the model and the remaining 0.30 used for model evaluation.…”
Section: Data Collectionmentioning
confidence: 99%
“…Past work on agronomic adaptation to climate change has primarily focused on field‐scale interventions such as changes to management and/or genotype/crop type combinations to improve yield (Ibrahim et al, 2019; Langworthy et al, 2018; Liu et al, 2021; Liu, Harrison, Hunt, et al, 2020) such as that aimed at closing yield gaps (Angella et al, 2016; Bryan et al, 2014; Liu et al, 2015, 2022; Muleke, Harrison, de Voil, et al, 2022; Pradhan et al, 2015). However, higher crop yields do not necessarily translate to higher crop profitability, because above a certain level of inputs, the rate of return from increased inputs diminishes (Ibrahim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%